Melioidosis in a Patient with Type I Diabetes Mellitus - A Case Report (Bangladesh Journal of Child Health, 2018)
Melioidosis is a relatively uncommon but fatal infectious disease caused by the gram negative bacterium, Burkholderia pseudomallei which is usually found in the wet soil, mud and pooled surface water in tropic and subtropics. Documented reports of melioidosis from Bangladesh have been few and sporadic. All of the reported cases in Bangladesh were on adult. Melioidosis is commonly associated with underlying diseases like diabetes mellitus, renal diseases and immunodeficiency disorders. Early and correct diagnosis is important, as mortality in untreated melioidosis is high. Our patient, an eleven years old boy, a known case of diabetes mellitus, presented with fever for one month associated with right sided neck swelling, abdominal distension & pain for 10 days. He had an abscess on the right side of the neck and hepatosplenomegaly. Ultrasonography of abdomen showed multiple abscesses in the liver and spleen. Culture of pus drained from the neck abscess revealed growth of Burkholderia pseudomallei. After getting parenteral antibiotics and insulin, his abscesses gradually resolved and cured completely.Bangladesh J Child Health 2018; VOL 42 (1) :46-48